Rural development in action : a case study of coastal areas - Giriappa, S. (Delhi : Daya Pub. House, 1993)
Case study of a region in Karnataka.
Includes bibliographical references and index.
Keywords: Rural development -- India -- Karnataka; Karnataka (India) -- Rural conditions